Islamic Education and Social Character Development in the Era of Globalization: Responding to Social Challenges in the Formation of a Moral Generation - Dasep Hanan Mubarok (CV. Intake Pustaka, 2025)
This article aims to analyze the role of Islamic education in shaping the social character of the younger generation in the era of globalization and how it can address the social challenges faced by modern society. This study employs a library research approach, gathering data from various relevant literature sources related to Islamic education, social character, and the challenges of globalization. Islamic education plays a significant role in social character formation by instilling deep moral values such as honesty, responsibility, empathy, and justice. It also contributes to countering the negative impacts of globalization, such as individualism and materialism. The findings of this study can be used to inform educational policies aimed at fostering social character formation in the context of Islam, providing guidance for educational institutions to design curricula that address social challenges and globalization.